Low-temperature co-fired ceramic tape casting slurry based on acrylic resin and preparation method thereof
By using thermoplastic acrylic resin with moderate weight average molecular weight and glass transition temperature as a binder in low-temperature cofiring ceramic technology, the problem of cross-linking reaction between polyvinyl butyral and borosilicate materials is solved, and the problem of cross-linking reaction between polyvinyl butyral and borosilicate materials is achieved. The good mechanical properties and stacking bonding of raw ceramic sheets ensure the stability and sintering density of the cast slurry.
Patent Information
- Application Number
- CN202411732307.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-02-18
AI Technical Summary
In the existing low-temperature co-fired ceramic technology, polyvinyl butyral and borosilicate materials are prone to cross-linking reactions, resulting in abnormally high viscosity or clumping of slurry, and the stacking binding force of the raw ceramic flakes is significantly attenuated, which affects the Process accuracy.
Using thermoplastic acrylic resin with moderate weight average molecular weight and glass transition temperature as the binder, a stable low-temperature co-fired ceramic casting slurry is prepared by adjusting the amount or proportion of the acrylic resin to ensure the casting of the raw ceramic sheets. Have good mechanical properties and stacking bonding force.
The stability and controllability of the cast slurry are achieved. The obtained raw ceramic sheets can still maintain good stacking bonding force and mechanical strength after being stored for more than 6 months, and have good sintering density.
Smart Images

Figure CN119462176A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of low-temperature co-fired ceramics, and in particular to a low-temperature co-fired ceramic tape casting slurry based on acrylic resin and a preparation method thereof. Background Art
[0002] Low Temperature Co-fired Ceramic (LTCC) technology is one of the core technologies for passive integration and packaging interconnection. It is to make green ceramic tape by casting the green ceramic powder of low-temperature sintered ceramics, and then make the required circuit graphics on the green ceramic tape by punching, filling holes, electrode printing and other processes. In addition, a variety of passive components (such as capacitors, resistors, filters, couplers, etc.) can be buried in a multilayer ceramic substrate, and then stacked together and sintered below 950°C to make a three-dimensional high-density circuit. It can also be made into a three-dimensional circuit substrate with built-in passive components, and ICs and active devices can be mounted on its surface to make a passive / active integrated functional module, which is particularly suitable for high-frequency communication components. Due to its excellent electrical, mechanical, thermal and process characteristics, low-temperature co-fired ceramic technology has become the core technology for miniaturization, integration and modularization of electronic components, and has been widely used in aviation, aerospace, military, automotive electronics, wireless communications and other fields.
[0003] Low-temperature co-fired ceramic tape casting slurry is an important part of low-temperature co-fired ceramic technology. It is mainly composed of low-temperature co-fired ceramic raw powder and organic carrier. The organic carrier includes solvent, dispersant, binder, plasticizer, etc. The organic carrier and low-temperature co-fired ceramic raw powder need to have good compatibility to obtain a stable tape casting slurry. The tape-cast raw ceramic sheets need to have good lamination bonding and mechanical properties. Among them, the binder plays a decisive role in the lamination bonding and mechanical properties of the raw ceramic sheets. Polyvinyl Butyral (PVB) has functional groups such as hydroxyl and acetal groups, so it has good comprehensive performance and is widely used in the entire ceramic tape casting field.
[0004] However, polyvinyl butyral and borosilicate low temperature co-fired ceramic materials are prone to cross-linking reaction, which can cause abnormally high viscosity of the slurry and even agglomeration, so that it is ultimately impossible to stabilize normal casting. In addition, the lamination bonding force of the raw porcelain sheets of polyvinyl butyral is significantly attenuated, and normal lamination cannot be performed after long-term storage. It is often necessary to spray glue before lamination, which increases the process difficulty. Acrylic resin has almost no hydroxyl functional groups and will not undergo cross-linking reaction with raw porcelain powder. In recent years, it has gradually received more attention. Patent applications such as publication numbers CN113045204A, CN113372103A, CN114276152A, and CN118754625A all mention the use of acrylic resin as a binder.
[0005] However, the molecular structure of acrylic resin is linear, which makes it difficult for raw ceramic sheets to obtain good mechanical properties and lamination bonding strength. During lamination, punching, cutting and other processes, delamination, cracking or deformation occurs, affecting the process accuracy, and even making it impossible to completely peel off from the PET carrier, which is very unfavorable for the use of raw ceramic sheets. By increasing the amount of acrylic resin added, better mechanical properties and lamination bonding strength can often be obtained, but too much addition will also lead to poor sintering density. Therefore, how to select the type and amount of acrylic resin to obtain raw ceramic sheets with excellent mechanical properties, lamination bonding strength and good sintering density is still a technical problem in the field of low-temperature co-fired ceramic technology. Summary of the invention
[0006] The purpose of the present invention is to overcome the problems of the prior art and provide a low-temperature co-fired ceramic tape-casting slurry based on acrylic resin and a preparation method thereof. The tape-casting slurry obtained by the preparation method is stable and has strong adaptability to low-temperature co-fired ceramic materials of different compositions. The tape-cast green ceramic sheets have good controllable mechanical properties and lamination bonding strength, and the green body has good sintering density.
[0007] In order to achieve the above object, the technical solution adopted by the present invention is as follows: A low-temperature co-fired ceramic tape-casting slurry based on acrylic resin, comprising low-temperature co-fired ceramic green porcelain powder, a binder, a plasticizer, a solvent and a dispersant; Based on the mass of low-temperature co-fired ceramic green powder as 100%, the binder is 10-20%, the plasticizer is 2-8%, the solvent is 50-120%, and the dispersant is 1-4%; The binder is one or more thermoplastic acrylic resins, the weight average molecular weight of the acrylic resin is 100,000 to 500,000, and the glass transition temperature is 30 to 80°C; When the binder is an acrylic resin, the weight average molecular weight is 250,000 to 400,000, and the glass transition temperature is 40 to 60°C; When the binder is a plurality of acrylic resins, a low glass transition temperature acrylic resin and a high glass transition temperature acrylic resin are combined, the glass transition temperature of the low glass transition temperature acrylic resin is 30 to 50°C, and the glass transition temperature of the high glass transition temperature acrylic resin is 50 to 80°C.
[0008] Furthermore, the average particle size D50 of the low-temperature co-fired ceramic green powder is 0.5-4 μm, and the viscosity of the low-temperature co-fired ceramic casting slurry is 500-2000 cps.
[0009] Furthermore, the plasticizer is one or more of triethylene glycol diisooctanoate, triethylene glycol diisooctanoate, polyethylene glycol-400, dibutyl phthalate, dioctyl phthalate, and benzyl butyl phthalate.
[0010] Furthermore, the solvent is one or more of xylene, toluene, ethyl acetate, propyl acetate, butyl acetate, isopropanol, butanone, and methyl isoamyl ketone.
[0011] Furthermore, the dispersant is at least one of triolein, tributyl phosphate, fish oil, oleic acid, AWS-0851, AKM0531, BYK-118, and NK2655.
[0012] A method for preparing a low-temperature co-fired ceramic tape-casting slurry based on acrylic resin, which is applied to any of the above-mentioned low-temperature co-fired ceramic tape-casting slurries based on acrylic resin, comprises the following steps: Mixing a solvent, a dispersant and low temperature co-fired ceramic green powder to obtain slurry A; Mixing a solvent, an acrylic resin binder and a plasticizer to obtain slurry B; Mixing slurry A and slurry B to obtain slurry C; The slurry C is filtered and degassed to obtain a low temperature co-fired ceramic tape casting slurry.
[0013] Furthermore, the mixing process is: the rotation speed is 100-500 r / min and the temperature is 25-40°C.
[0014] Furthermore, the mixing time of slurry A is 1 to 5 hours, the mixing time of slurry B is 1 to 3 hours, and the mixing time of slurry C is 3 to 6 hours.
[0015] Furthermore, the degassing process is: mixing for 1 to 4 hours at a vacuum degree greater than -0.095 MPa, a stirring speed of 10 to 50 r / min, and a temperature of 25°C.
[0016] Furthermore, the mixing method is ball milling mixing.
[0017] Compared with the prior art, the present invention adopts a thermoplastic acrylic resin with a moderate weight average molecular weight and glass transition temperature as a binder, and adjusts the amount or ratio of the acrylic resin therein, so that the obtained casting slurry is stable and controllable, and the green porcelain sheet obtained by casting has good mechanical properties and lamination bonding strength, and also has better adaptability to different types of green porcelain powder. The green porcelain sheet prepared by the present invention can still achieve good lamination bonding strength and mechanical strength after being stored for more than 6 months. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 The figure is a schematic flow chart of a method for preparing a low-temperature co-fired ceramic tape-casting slurry based on acrylic resin.
[0019] Figure 2 The peeling condition of the green ceramic sheet prepared in Example 1 is shown.
[0020] Figure 3 This is the cross-sectional microscopic morphology of the green ceramic sheets after lamination, cutting and sintering in Example 1.
[0021] Figure 4 This is the peeling condition of the green ceramic sheet prepared in Comparative Example 1.
[0022] Figure 5 This is the cross-sectional microscopic morphology of the raw ceramic sheets in Comparative Example 3 after lamination, cutting and sintering. DETAILED DESCRIPTION
[0023] The low temperature co-fired ceramic tape casting slurry based on acrylic resin and the preparation method thereof are further described below in conjunction with the accompanying drawings and specific embodiments.
[0024] The present invention provides a low-temperature co-fired ceramic tape-casting slurry based on acrylic resin, comprising low-temperature co-fired ceramic green porcelain powder, a binder, a plasticizer, a solvent and a dispersant. The binder is one or more thermoplastic acrylic resins, the weight average molecular weight of the acrylic resin is 100,000 to 500,000, and the glass transition temperature is 30 to 80°C. Selecting one or more acrylic resins of this type can make the tape-casting slurry more stable, and the green porcelain sheet obtained by tape-casting has good lamination bonding force, mechanical strength, sintering shrinkage and sintering density when used normally at room temperature.
[0025] When the binder is a single acrylic resin, the weight average molecular weight is 250,000 to 400,000, and the glass transition temperature is 40 to 60° C. When the binder is a plurality of acrylic resins, a combination of a low glass transition temperature acrylic resin and a high glass transition temperature acrylic resin is used, the glass transition temperature of the low glass transition temperature acrylic resin is 30 to 50° C., and the glass transition temperature of the high glass transition temperature acrylic resin is 50 to 80° C.
[0026] In a specific embodiment, when an acrylic resin is used in the casting slurry, the weight average molecular weight is 250,000 to 400,000, and the glass transition temperature is 40 to 60°C. In this way, a green sheet with good mechanical strength, lamination bonding strength, sintering shrinkage and sintering density can be obtained at a relatively low addition amount. When the molecular weight is too small or the glass transition temperature is too high, the strength of the cast green sheet is low; when the molecular weight is too large, the sintering density is easily deteriorated due to the difficulty of debinding, and when the glass transition temperature is too high, the plasticity of the cast green sheet is poor and the processing performance is deteriorated.
[0027] In a specific embodiment, when multiple acrylic resins are used in the casting slurry, the combination should be low glass transition temperature acrylic resin + high glass transition temperature acrylic resin, the glass transition temperature of the low glass transition temperature acrylic resin is 30-50°C, and the glass transition temperature of the high glass transition temperature acrylic resin is 50-80°C, so that a green sheet with good mechanical strength, lamination bonding strength, sintering shrinkage and sintering density can be obtained at a relatively low addition amount. Adding green sheets with a glass transition temperature higher than 80°C or lower than 30°C will deteriorate the mechanical strength of the green sheet and the processing performance.
[0028] In a specific embodiment, the mass of the low-temperature co-fired ceramic green porcelain powder is 100%, and the binder is 10-20%, so that the tensile strength of the green porcelain sheet, the sintering shrinkage rate of the material and the sintering density can be better balanced. If the mass ratio of the binder is too high, the sintering shrinkage rate of the material will be too large and the sintering density will be poor. If the mass ratio is too low, the tensile strength of the green porcelain sheet will be low or even cracking will occur during the casting process.
[0029] In a specific embodiment, the acrylic resin is added in the form of a solution with a mass concentration of 25 to 50%, and the solvent used is the same as the solvent of the casting slurry. This ensures that the binder solution is easier to obtain and is conducive to the preparation of the subsequent casting slurry. If the concentration of the binder solution is too high, it will not be fully dissolved, and if the concentration of the binder solution is too low, the amount of solvent added when preparing the slurry will be insufficient to wet the ceramic green powder.
[0030] In a specific embodiment, the plasticizer is 2-8% based on the mass of the low-temperature co-fired ceramic green porcelain powder as 100%, so that the tensile strength and process adaptability of the green porcelain sheet can be comprehensively balanced. If the mass ratio is too high, it is easy to cause problems such as low tensile strength and large deformation of the green sheet during lamination. If the mass ratio is too low, it is easy to cause the plasticity of the green porcelain sheet to deteriorate, and defects such as broken edges and burrs appear during the green cutting process.
[0031] The plasticizer can be selected from one or more of triethylene glycol diisooctanoate, triethylene glycol diisooctanoate, polyethylene glycol-400, dibutyl phthalate, dioctyl phthalate, benzyl butyl phthalate, preferably a binary mixture of triethylene glycol diisooctanoate and polyethylene glycol-400 in a weight ratio of 1:1.
[0032] In a specific embodiment, the solvent is 50-120% based on the mass of the low-temperature co-fired ceramic green porcelain powder as 100%, so that a slurry with suitable viscosity and good dispersibility and a green porcelain sheet with better quality can be obtained. If the mass ratio is too high, the amount of solvent volatilization during the casting process is large, and cracking and other problems are prone to occur. If the mass ratio is too low, it will make it difficult for the slurry to be thoroughly wetted and evenly dispersed, and it may cause the slurry viscosity to be too high, resulting in poor quality of the green porcelain sheet.
[0033] The solvent can be selected from one or more of xylene, toluene, ethyl acetate, propyl acetate, butyl acetate, isopropanol, butanone, and methyl isoamyl ketone, preferably a mixture of xylene and propyl acetate in a weight ratio of 1:1, so that the slurry and the cast green porcelain sheet can be more stable.
[0034] In a specific embodiment, the mass ratio of the low temperature co-fired ceramic green powder is 100%, and the dispersant is 1-4%, so that a slurry with good stability can be obtained. Too high or too low mass ratio will lead to poor slurry stability.
[0035] The dispersant may be selected from those commonly used in the industry, preferably at least one of triolein, tributyl phosphate, fish oil, oleic acid, AWS-0851, AKM0531, BYK-118, and NK2655.
[0036] In a specific embodiment, the average particle size or median diameter D50 of the low temperature co-fired ceramic green powder is 0.5-4 μm, and the viscosity of the low temperature co-fired ceramic casting slurry is controlled to be 500-2000 cps.
[0037] See also Figure 1 The present invention also provides a method for preparing a low temperature co-fired ceramic tape casting slurry based on acrylic resin, which specifically comprises the following steps: (1) Adding a solvent, a dispersant and a low-temperature co-fired ceramic green powder into a feeding tank A in sequence, and mixing to obtain a slurry A, the mixing process is: a rotation speed of 100 to 500 r / min, a temperature of 25 to 40° C.; the mixing method is ball milling, and the mixing time of the slurry A is 1 to 5 hours.
[0038] (2) Adding a solvent, an acrylic resin binder and a plasticizer to a feed tank B in sequence, and mixing to obtain slurry B, the mixing process is as follows: a rotation speed of 100 to 500 r / min, a temperature of 25 to 40° C.; the mixing method is ball milling, and the mixing time of slurry B is 1 to 3 hours.
[0039] (3) The prepared slurry A and slurry B are mixed to obtain slurry C. The mixing process is as follows: the rotation speed is 100 to 500 r / min, the temperature is 25 to 40° C.; the mixing method is ball milling, and the mixing time of slurry C is 3 to 6 hours.
[0040] (4) The obtained slurry C is filtered and transferred to a vacuum degassing tank for degassing to obtain a low-temperature co-fired ceramic tape casting slurry. The degassing process is: mixing for 1 to 4 hours at a vacuum degree greater than -0.095 MPa, a stirring speed of 10 to 50 r / min, and a temperature of 25°C.
[0041] The low temperature co-fired ceramic tape casting slurry based on acrylic resin and the preparation method thereof are described in detail below by listing some specific embodiments.
[0042] Example 1 (1) 1300 g of xylene, 1300 g of ethyl acetate, 100 g of tributyl phosphate, and 5000 g of low-temperature co-fired ceramic green powder were added to a feed tank A in sequence, and then mixed at a speed of 500 r / min and a temperature of 25° C. for 2 hours to obtain slurry A.
[0043] (2) 735 g of xylene, 735 g of ethyl acetate, 630 g of acrylic resin B48N, 100 g of triethylene glycol diisooctanoate, and 100 g of polyethylene glycol-400 were added to feed tank B in sequence, and then mixed at a speed of 500 r / min and a temperature of 25° C. for 3 hours to obtain slurry B.
[0044] (3) Slurry A and slurry B were mixed at a rotation speed of 500 r / min and a temperature of 25° C. for 3 hours to obtain slurry C.
[0045] (4) The obtained slurry C was filtered and transferred to a vacuum degassing tank, and then continued to be mixed and degassed for 2 hours at a vacuum degree greater than -0.095 MPa, a stirring speed of 10 to 50 r / min and a temperature of 25°C to obtain a low-temperature co-fired ceramic tape casting slurry.
[0046] The casting slurry prepared in Example 1 was introduced into the hopper of the casting machine, and the casting machine was turned on to prepare the casting green ceramic sheet. During the casting process, the scraper height was controlled at 400 μm, and the casting speed was 2 m / min. The prepared green ceramic sheet could be completely peeled off from the PET film (polyester substrate), as shown in FIG. Figure 2 As shown. The tensile strength is 2.1MPa, the elongation at break is 16%, and after lamination, it is cut into green pieces of 40mm*40mm*1mm. The green pieces have good sintering density, such as Figure 3 shown.
[0047] Example 2 (1) Into a feed tank A, 1200 g of xylene, 1200 g of ethyl acetate, 100 g of tributyl phosphate, and 5500 g of low-temperature co-fired ceramic green powder were added in sequence, and then mixed at a speed of 500 r / min and a temperature of 25° C. for 2 hours to obtain slurry A.
[0048] (2) Into feeding tank B, 585 g of xylene, 585 g of ethyl acetate, 480 g of acrylic resin LP62 / 05, 150 g of acrylic resin P24, 100 g of triethylene glycol diisooctanoate, and 100 g of polyethylene glycol-400 were added in sequence, and then mixed at a speed of 500 r / min and a temperature of 25°C for 3 hours to obtain slurry B.
[0049] (3) Slurry A and slurry B were mixed at a rotation speed of 500 r / min and a temperature of 25° C. for 3 hours to obtain slurry C.
[0050] (4) The obtained slurry C was filtered and transferred to a vacuum degassing tank, and then continued to be mixed and degassed for 2 hours at a vacuum degree greater than -0.095 MPa, a stirring speed of 10 to 50 r / min and a temperature of 25°C to obtain a low-temperature co-fired ceramic tape casting slurry.
[0051] The casting slurry prepared in Example 2 was introduced into the hopper of the casting machine, and the casting machine was turned on to prepare the casting green porcelain sheet. During the casting process, the scraper height was controlled at 400 μm and the casting speed was 2 m / min. The prepared green porcelain sheet could be completely peeled off from the PET film (polyester substrate), with a tensile strength of 1.8 MPa and an elongation at break of 18%. The lamination bonding strength and sintering density were both good.
[0052] Example 3 (1) Into a feed tank A, 1250 g of xylene, 1250 g of ethyl acetate, 100 g of tributyl phosphate, and 5000 g of low-temperature co-fired ceramic green powder were added in sequence, and then mixed at a speed of 500 r / min and a temperature of 25° C. for 2 hours to obtain slurry A.
[0053] (2) Into feeding tank B, 770 g of xylene, 770 g of ethyl acetate, 165 g of acrylic resin B66, 165 g of acrylic resin B72, 330 g of acrylic resin B48N, 100 g of triethylene glycol diisooctanoate, and 100 g of polyethylene glycol-400 were added in sequence, and then mixed at a speed of 500 r / min and a temperature of 25°C for 3 hours to obtain slurry B.
[0054] (3) Slurry A and slurry B were mixed at a speed of 500 r / min and a temperature of 25° C. for 3 hours to obtain slurry C.
[0055] (4) The obtained slurry C was filtered and transferred to a vacuum degassing tank, and then continued to be mixed and degassed for 2 hours at a vacuum degree greater than -0.095 MPa, a stirring speed of 10 to 50 r / min and a temperature of 25°C to obtain a low-temperature co-fired ceramic tape casting slurry.
[0056] The casting slurry prepared in Example 3 was introduced into the hopper of the casting machine, and the casting machine was turned on to prepare the casting green porcelain sheet. During the casting process, the scraper height was controlled at 400 μm and the casting speed was 2 m / min. The prepared green porcelain sheet could be completely peeled off from the PET film (polyester substrate), with a tensile strength of 1.6 MPa and an elongation at break of 19%. The lamination bonding strength and sintering density were both good.
[0057] Example 4 (1) Into a feed tank A, 1350 g of xylene, 1350 g of ethyl acetate, 100 g of tributyl phosphate, and 5000 g of low-temperature co-fired ceramic green powder were added in sequence, and then mixed at a speed of 500 r / min and a temperature of 25° C. for 2 hours to obtain slurry A.
[0058] (2) 700 g of xylene, 700 g of ethyl acetate, 300 g of acrylic resin B82, 200 g of acrylic resin LP62 / 05, 100 g of triethylene glycol diisooctanoate, and 100 g of polyethylene glycol-400 were added to feeding tank B in sequence, and then mixed at a speed of 500 r / min and a temperature of 25°C for 3 hours to obtain slurry B.
[0059] (3) Slurry A and slurry B were mixed at a speed of 500 r / min and a temperature of 25° C. for 3 hours to obtain slurry C.
[0060] (4) The obtained slurry C was filtered and transferred to a vacuum degassing tank, and then continued to be mixed and degassed for 2 hours at a vacuum degree greater than -0.095 MPa, a stirring speed of 10 to 50 r / min and a temperature of 25°C to obtain a low-temperature co-fired ceramic tape casting slurry.
[0061] The casting slurry prepared in Example 4 was introduced into the hopper of the casting machine, and the casting machine was turned on to prepare the casting green porcelain sheet. During the casting process, the scraper height was controlled at 400 μm and the casting speed was 2 m / min. The prepared green porcelain sheet could be completely peeled off from the PET film (polyester substrate), with a tensile strength of 2.3 MPa and an elongation at break of 15%. The lamination bonding strength and sintering density were both good.
[0062] Comparative Example 1 (1) Into a feed tank A, 1350 g of xylene, 1350 g of ethyl acetate, 100 g of tributyl phosphate, and 5000 g of low-temperature co-fired ceramic green powder were added in sequence, and then mixed at a speed of 500 r / min and a temperature of 25° C. for 2 hours to obtain slurry A.
[0063] (2) 700 g of xylene, 700 g of ethyl acetate, 600 g of acrylic resin B72, 100 g of triethylene glycol diisooctanoate, and 100 g of polyethylene glycol-400 were added to feeding tank B in sequence, and then mixed at a speed of 500 r / min and a temperature of 25° C. for 3 hours to obtain slurry B.
[0064] (3) Slurry A and slurry B were mixed at a rotation speed of 500 r / min and a temperature of 25° C. for 3 hours to obtain slurry C.
[0065] (4) The slurry C obtained in step (3) is filtered and transferred to a vacuum degassing tank, and then mixed and degassed for 2 hours at a vacuum degree greater than -0.095 MPa, a stirring speed of 10 to 50 r / min and a temperature of 25°C to obtain a low-temperature co-fired ceramic tape casting slurry.
[0066] The casting slurry prepared in Comparative Example 1 was introduced into the hopper of the casting machine, and the casting machine was turned on to prepare the casting green ceramic sheet. During the casting process, the scraper height was controlled at 400 μm, and the casting speed was 2 m / min. The prepared green ceramic sheet could not be completely peeled off from the PET film (polyester substrate), and the mechanical properties were poor. Figure 4 shown.
[0067] Comparative Example 2 (1) Into a feed tank A, 1650 g of xylene, 1650 g of ethyl acetate, 100 g of tributyl phosphate, and 4000 g of low-temperature co-fired ceramic green powder were added in sequence, and then mixed at a speed of 500 r / min and a temperature of 25° C. for 2 hours to obtain slurry A.
[0068] (2) 790 g of xylene, 790 g of ethyl acetate, 820 g of acrylic resin B72, 100 g of triethylene glycol diisooctanoate, and 100 g of polyethylene glycol-400 were added to feed tank B in sequence, and then mixed at a speed of 500 r / min and a temperature of 25°C for 3 hours to obtain slurry B.
[0069] (3) Slurry A and slurry B were mixed at a rotation speed of 500 r / min and a temperature of 25° C. for 3 hours to obtain slurry C.
[0070] (4) The obtained slurry C was filtered and transferred to a vacuum degassing tank, and then continued to be mixed and degassed for 2 hours at a vacuum degree greater than -0.095 MPa, a stirring speed of 10 to 50 r / min and a temperature of 25°C to obtain a low-temperature co-fired ceramic tape casting slurry.
[0071] The casting slurry prepared in Comparative Example 2 was introduced into the hopper of the casting machine, and the casting machine was turned on to prepare the casting green ceramic sheet. During the casting process, the scraper height was controlled at 400 μm, and the casting speed was 2 m / min. The prepared green ceramic sheet could be completely peeled off from the PET film (polyester substrate), with a tensile strength of 0.7 MPa and an elongation at break of 40%. The density became poor after sintering, such as Figure 5 shown.
[0072] Comparative Example 3 (1) Into a feed tank A, 1350 g of xylene, 1350 g of ethyl acetate, 100 g of tributyl phosphate, and 5000 g of low-temperature co-fired ceramic green powder were added in sequence, and then mixed at a speed of 500 r / min and a temperature of 25° C. for 2 hours to obtain slurry A.
[0073] (2) 700 g of xylene, 700 g of ethyl acetate, 600 g of acrylic resin BR-85, 100 g of triethylene glycol diisooctanoate, and 100 g of polyethylene glycol-400 were added to feed tank B in sequence, and then mixed at a speed of 500 r / min and a temperature of 25°C for 3 hours to obtain slurry B.
[0074] (3) Slurry A and slurry B were mixed at a rotation speed of 500 r / min and a temperature of 25° C. for 3 hours to obtain slurry C.
[0075] (4) The obtained slurry C was filtered and transferred to a vacuum degassing tank, and then continued to be mixed and degassed for 2 hours at a vacuum degree greater than -0.095 MPa, a stirring speed of 10 to 50 r / min and a temperature of 25°C to obtain a low-temperature co-fired ceramic tape casting slurry.
[0076] The casting slurry prepared in Comparative Example 3 was introduced into the hopper of the casting machine, and the casting machine was turned on to prepare the casting raw ceramic sheet. During the casting process, the scraper height was controlled at 400 μm and the casting speed was 2 m / min. The prepared raw ceramic sheet could not be completely peeled off from the PET film (polyester substrate) and had poor mechanical properties.
[0077] Comparative Example 4 (1) Into a feed tank A, 1350 g of xylene, 1350 g of ethyl acetate, 100 g of tributyl phosphate, and 5000 g of low-temperature co-fired ceramic green powder were added in sequence, and then mixed at a speed of 500 r / min and a temperature of 25° C. for 2 hours to obtain slurry A.
[0078] (2) 700 g of xylene, 700 g of ethyl acetate, 600 g of acrylic resin Elvacite 2044, 100 g of triethylene glycol diisooctanoate, and 100 g of polyethylene glycol-400 were added to feed tank B in sequence, and then mixed at a speed of 500 r / min and a temperature of 25° C. for 3 hours to obtain slurry B.
[0079] (3) Slurry A and slurry B were mixed at a rotation speed of 500 r / min and a temperature of 25° C. for 3 hours to obtain slurry C.
[0080] (4) The obtained slurry C was filtered and transferred to a vacuum degassing tank, and then continued to be mixed and degassed for 2 hours at a vacuum degree greater than -0.095 MPa, a stirring speed of 10 to 50 r / min and a temperature of 25°C to obtain a low-temperature co-fired ceramic tape casting slurry.
[0081] The casting slurry prepared in Comparative Example 4 was introduced into the hopper of the casting machine, and the casting machine was turned on to prepare the casting raw ceramic sheet. During the casting process, the scraper height was controlled at 400 μm and the casting speed was 2 m / min. The prepared raw ceramic sheet could not be completely peeled off from the PET film (polyester substrate) and had poor mechanical properties.
[0082] Comparative Example 5 (1) Into a feed tank A, 1350 g of xylene, 1350 g of ethyl acetate, 100 g of tributyl phosphate, and 5000 g of LTCC raw porcelain powder were added in sequence, and then mixed at a speed of 500 r / min and a temperature of 25° C. for 2 hours to obtain slurry A.
[0083] (2) Add 700 g of xylene, 700 g of ethyl acetate, 300 g of acrylic resin B82, 300 g of acrylic resin BR-85, 100 g of triethylene glycol diisooctanoate, and 100 g of polyethylene glycol-400 to feeding tank B in sequence, and then mix at a speed of 500 r / min and a temperature of 25°C for 3 hours to obtain slurry B.
[0084] (3) Slurry A and slurry B were mixed at a speed of 500 r / min and a temperature of 25° C. for 3 hours to obtain slurry C.
[0085] (4) The slurry C obtained in step (3) is filtered and transferred to a vacuum degassing tank, and then mixed and degassed for 2 hours at a vacuum degree greater than -0.095 MPa, a stirring speed of 10 to 50 r / min and a temperature of 25°C to obtain a low-temperature co-fired ceramic tape casting slurry.
[0086] The casting slurry prepared in Comparative Example 5 was introduced into the hopper of the casting machine, and the casting machine was turned on to prepare the casting raw ceramic sheet. During the casting process, the scraper height was controlled at 400 μm and the casting speed was 2 m / min. The prepared raw ceramic sheet could not be completely peeled off from the PET film and had poor mechanical properties.
[0087] Table 1 shows the molecular weight and glass transition temperature of the binder acrylic resin used in the above examples and comparative examples, and Table 2 shows the performance summary of the green ceramic sheets in the above examples and comparative examples.
[0088] Table 1 Molecular weight and glass transition temperature of acrylic resin binder in Examples and Comparative Examples Table 2 Properties of raw ceramic sheets in the examples and comparative examples It can be seen that the molecular weight, glass transition temperature and dosage of the binder acrylic resin have a significant impact on the green ceramic sheet. In Example 1, an acrylic resin B48N with a weight average molecular weight of 250,000, a glass transition temperature of 50°C, and an addition amount of 12.6wt% of the powder is used, and the final green ceramic sheet has better performance. In Examples 2 to 4, a variety of acrylic resins are used, respectively composed of acrylic resins P24N, B72, B82 with low glass transition temperatures and acrylic resins LP62 / 5, B66, B48N with high glass transition temperatures. The performance of the cast green sheet is also better.
[0089] In Comparative Example 1, an acrylic resin B72 is used, and its weight-average molecular weight is lower than 250,000. The mechanical strength of the raw sheet is low and it cannot be peeled off in one piece. In Comparative Example 2, an acrylic resin B48N is used, and its weight-average molecular weight and glass transition temperature are both within the preferred range, but the addition amount is higher than 20wt%, and the number of holes increases after sintering. Comparative Examples 3 to 4 use an acrylic resin, but the glass transition temperature is not in the range of 40 to 60°C, and the mechanical strength of the raw sheet is low, and it cannot be peeled off in one piece. Comparative Example 5 uses a low glass transition temperature acrylic resin B82 and a high glass transition temperature acrylic resin BR-85, wherein the glass transition temperature of BR-85 is higher than 80°C, and the strength of the raw sheet is low, and it cannot be peeled off in one piece.
[0090] In summary, the present invention adopts a thermoplastic acrylic resin with a moderate weight average molecular weight and glass transition temperature as a binder, and by adjusting the amount or ratio of the acrylic resin, it also has better adaptability to different types of raw porcelain powders, the casting slurry is stable and controllable, and the obtained raw porcelain sheet has good mechanical properties and lamination bonding strength. The raw porcelain sheet prepared by the present invention can still achieve good lamination bonding strength and mechanical strength after being stored for more than 6 months.
[0091] The above description is a detailed description of the preferred feasible embodiments of the present invention, but the embodiments are not intended to limit the scope of the patent application of the present invention. All equivalent changes or modified changes completed under the technical spirit disclosed by the present invention should fall within the patent scope covered by the present invention.
Claims
1. A low temperature co-fired ceramic tape casting slurry based on acrylic resin, characterized in that: Including low temperature co-fired ceramic green porcelain powder, binder, plasticizer, solvent and dispersant; Based on the mass of low-temperature co-fired ceramic green powder as 100%, the binder is 10-20%, the plasticizer is 2-8%, the solvent is 50-120%, and the dispersant is 1-4%; The binder is one or more thermoplastic acrylic resins, the weight average molecular weight of the acrylic resin is 100,000 to 500,000, and the glass transition temperature is 30 to 80°C; When the binder is an acrylic resin, the weight average molecular weight is 250,000 to 400,000, and the glass transition temperature is 40 to 60°C; When the binder is a plurality of acrylic resins, a low glass transition temperature acrylic resin and a high glass transition temperature acrylic resin are combined, the glass transition temperature of the low glass transition temperature acrylic resin is 30 to 50°C, and the glass transition temperature of the high glass transition temperature acrylic resin is 50 to 80°C.
2. The low temperature co-fired ceramic tape casting slurry based on acrylic resin according to claim 1, characterized in that: The average particle size D50 of the low-temperature co-fired ceramic green powder is 0.5-4 μm, and the viscosity of the low-temperature co-fired ceramic casting slurry is 500-2000 cps.
3. The low temperature co-fired ceramic tape casting slurry based on acrylic resin according to claim 1, characterized in that: The plasticizer is one or more of triethylene glycol diisooctanoate, triethylene glycol diisooctanoate, polyethylene glycol-400, dibutyl phthalate, dioctyl phthalate, and benzyl butyl phthalate.
4. The low temperature co-fired ceramic tape casting slurry based on acrylic resin according to claim 1, characterized in that: The solvent is one or more of xylene, toluene, ethyl acetate, propyl acetate, butyl acetate, isopropanol, butanone, and methyl isoamyl ketone.
5. The acrylic resin-based low-temperature co-fired ceramic tape casting slurry according to claim 1, characterized in that: The dispersant is at least one of triolein, tributyl phosphate, fish oil, oleic acid, AWS-0851, AKM0531, BYK-118, and NK2655.
6. A method for preparing a low-temperature co-fired ceramic tape-casting slurry based on acrylic resin, applied to the low-temperature co-fired ceramic tape-casting slurry based on acrylic resin according to any one of claims 1 to 5, characterized in that: The following steps are involved: Mixing a solvent, a dispersant and low temperature co-fired ceramic green powder to obtain slurry A; Mixing a solvent, an acrylic resin binder and a plasticizer to obtain slurry B; Mixing slurry A and slurry B to obtain slurry C; The slurry C is filtered and degassed to obtain a low temperature co-fired ceramic tape casting slurry.
7. The method for preparing a low temperature co-fired ceramic tape casting slurry based on acrylic resin according to claim 6, characterized in that: The mixing process is: the rotation speed is 100-500r / min and the temperature is 25-40°C.
8. The method for preparing low temperature co-fired ceramic tape casting slurry based on acrylic resin according to claim 6, characterized in that: The mixing time of slurry A is 1 to 5 hours, the mixing time of slurry B is 1 to 3 hours, and the mixing time of slurry C is 3 to 6 hours.
9. The method for preparing low temperature co-fired ceramic tape casting slurry based on acrylic resin according to claim 6, characterized in that: The degassing process is: mixing for 1 to 4 hours at a vacuum degree greater than -0.095 MPa, a stirring speed of 10 to 50 r / min, and a temperature of 25°C.
10. The method for preparing low temperature co-fired ceramic tape casting slurry based on acrylic resin according to claim 6, characterized in that: The mixing method is ball milling.
Citation Information
Patent Citations
Low-loss low-temperature co-fired ceramic green tape and preparation method thereof
CN113045204A
Low-dielectric low-high-frequency-loss LTCC material and preparation method thereof
CN113372103A
Adhesive for tape casting of low-temperature co-fired ceramic material and preparation method of adhesive
CN114276152A
Slurry for low-temperature co-fired ceramic and preparation method thereof
CN118754625A
Cited By
Self-plasticizing binder for non-aqueous tape casting and preparation method thereof
CN121362545A